The Image Transformations in the Pastoral Scene in Pre-Islamic Poetry - Alrfooh, Khaleel Abed Salem (Dirasat: Human and Social Sciences, 2025)
Objectives: This research aims to uncover the vision of the pre-Islamic poets and their perception of the changes that occurred to ruins after their inhabitants departed from them. It explores how the poets managed to artistically portray the remaining elements in the ruins and link these changes to the poet’s stance on existence, life, and death. The research also aims to depict an image of everything seen in the ruins, such as monsters, birds, tents, stakes, and others and what they were compared to. Methods: This research follows the descriptive-analytical method in observing the transformations depicted by the pre-Islamic poets, following a thorough examination of all pre-Islamic poetry in its known sources. Then analyze it and explain the artistic images within it. Results: The study resulted in a set of important findings, among which is that the transformations in the landscape of the “home” were profoundly distressing. This represents the tragedy experienced by the poets as they perceived the transition of habitable and joyous places into desolate ruins, devoid of anything but remnants symbolizing the absence of humanity and its inevitable fate of death. Conclusions: The study recommends future researchers to give significant attention to depicting the remnants in ruins and to delve into the phenomenon of poets’ contemplation of ruins. It suggests exploring pre-Islamic poetry for anything related to the transformations that occurred in places after their inhabitants departed, and whether there are reasons beyond those mentioned in the research for their departure.